“Intervención Psicopedagógica en estudiantes con Disgrafía en la Unidad Educativa Mario Paltin Lavanda de tercer grado periodo lectivo 2023-2024” - Chicaiza Delgado, Silvana Alexandra (2024)
The present curricular integration paper highlights the psycho-pedagogical intervention in students with dysgraphia. The general objective of the study is: To propose and apply didactic strategies in the language and literature department from the Unidad Educativa Mario Paltin Lavanda, to teach third-grade students with Dysgraphia disorder, period 2023 – 2024. It was supported by three specific objectives: the first one was to Implement didactic strategies aimed at enhancing the children’s learning, the second was to describe the basic characteristics of the Dysgraphia disorder in students, and the third was to devise a proposal for psycho-pedagogical educational intervention in students with Dysgraphia based on the results found in the research. The research applied was of a descriptive type, and a non-experimental design, with a mixed approach to understand and observe the sample population studied in its natural environment. In addition, the scientific, descriptive, inductive, analytical and statistical methods were used; the techniques used were the interview and the pre- and post-evaluation; Also, the instruments implemented were the pre- and post-evaluation questionnaire and the observation sheet, which contributed effectively to data collection, the people that participated in this study comprised 3 teachers and 49 students, who were selected by means of a non-probabilistic sampling by convenience. The results found evidenced that psycho-pedagogical intervention is vital in the school environment to address students with learning disorders. In addition, students with learning disorders such as dysgraphia, should be supported through focused strategies to guarantee an optimal learning process.